MONITORING LABORATORY SCALE RIVER CHANNEL PROFILE CHANGES USING DIGITAL CLOSE RANGE PHOTOGRAMMETRY TECHNIQUE (Malaysian Journal of Civil Engineering, 2018)
Measuring and monitoring of river channel evolution or changes under laboratory conditions is an important scope in hydraulic assessment. Measurement such as changes in river channel profile for instance, provides an important indicator on erosion and accretion rates in hydraulic modelling. Under controlled conditions, the changes in channel profile are usually measured using a high precision point gauge. However, when large numbers of points of river profile need to be measured, the use of point gauge method becomes laborious and time consuming. This study proposed a digital close range photogrammetry technique to measure natural river channel bed profile changes in laboratory. The objective of this study was to investigate the changes of physical river model profile for pre and post flooding simulations using digital close range photogrammetry technique. Small scale physical model experimental works were conducted in the Hydraulics and Hydrology Laboratory to observe the river profile evolution during the events. The flood flume utilized in this study is 4.95 m long, 1.38 m wide and 1.26 m deep with carved V-shaped natural main channel with a bed slope of 1:500. Data measured from digital close range photogrammetry technique during pre-flooding at t = 0 second and post flooding events at t= 9660 second were compared to determine the channel profile evolution or changes after simulation of flood event. The results show the changes in invert level or bed level between non-flooding and flooding events due to erosion is varies from 1 mm (minimum) to 6 mm (maximum) along the channel between chainage 0mm and chainage 2000 mm with total volume of erosion is 1157 x 103 mm3 respectively. It can be concluded that the digital close range photogrammetry technique can be used as a complimentary method to measure and monitor the changes of river channel profile in the laboratory